Consulting project for the lubricants export department of Galp Energia: global market assessment and redefinition of the internationalization strategy - Guerreiro, Francisco Fonseca Pires Duarte (2014)
The subsequent report is aimed at describing the group project conducted under the Management Consulting Field Labs initiative. It consisted of, as the name indicates, a consulting project completed by four NOVA SBE’s students for the Oil and Gas Company Galp Energia (Galp)on its Lubricants Export Department(Export Department). The project’s main objective was to develop a global market assessment and redefine Galp’s Lubricants Export Department internalization strategy. In order to respond to the Company’s needs, having in consideration the dimension of the scope, a high level approach was adopted. Furthermore, the close relationship with the client was critical in order to develop a project that matches the Export Department’s specific needs and therefore creating value for the client.